ZADIE SMITH’IN WHITE TEETH ROMANINDA “TARİH” VE “KÖKEN” - Seda ARIKAN (Fırat University, 2019)
The debut novel of Zadie Smith, White Teeth, handles the notions of “history” and “root” momentously. The novel, which presents the characters’ past and root with many minor stories, functions as a historical bond connecting the past to the present and the future. As a postcolonial and multicultural novel, White Teeth presents historical consciousness in two-dimensional manner; racial history and personal history. By depicting the stories of immigrant and multi-ethnic families of the novel, Zadie Smith reveals a racial history which examines the colonial background of Britain as a colonizer. In White Teeth, this racial and colonial history is related to the familial and personal one and by this way how history and root affect the first and second generation immigrant and multi-ethnic families is questioned in a critical way. In this respect, this study examines the place and significance of “history” and “root” in the life of multi-ethnic and/or immigrant families and their racially and/or culturally hybrid children in White Teeth. In the study, the notions of “history” and “root” are handled related to the racial and personal stories of the characters. That’s why; the characters’ relation to their racial, familial and personal history, their search for a historical identity, the difficulties and dilemmas they experience in the process of gaining a historical consciousness and how much they achieve to form a historical consciousness and root in their lives will be presented as significant determiners in this study.